2012
DOI: 10.1111/j.1538-7836.2012.04863.x
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin complex concentrates reduce blood loss in murine coagulopathy induced by warfarin, but not in that induced by dabigatran etexilate

Abstract: Summary.  Background:  Both established oral anticoagulants such as warfarin and newer agents such as dabigatran etexilate (DE) effectively prevent thromboembolic disease, but may provoke bleeding. Limited clinical data exist linking oral anticoagulant reversal and bleeding tendency, as opposed to surrogate laboratory markers. Objective:  To quantify bleeding in warfarin‐anticoagulated and DE‐anticoagulated mice by tail transection with or without pretreatment with potential reversal agents: prothrombin comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 45 publications
(64 reference statements)
2
81
0
1
Order By: Relevance
“…PCCs are the preferred nonspecific hemostatic agent for NOAC reversal; they are plasma-derived products that contain three (factors II, IX, and X) or four (factors II, IX, X, and VII) clotting factors, in addition to variable amounts of heparin and the natural coagulation inhibitors protein C and protein S. Animal studies have demonstrated that PPCs have a variable ability to normalize anticoagulation parameters and to prevent or attenuate bleeding seen with NOAC usage. 14,[19][20][21][22][23][24][25] The limited data available in humans are restricted to healthy volunteers only. In three small, randomized, placebo-controlled studies involving between 12 and 93 patients, PCC use reversed the anticoagulant effects of rivaroxaban and edoxaban, but not of dabigatran.…”
Section: General Supportive Measuresmentioning
confidence: 99%
“…PCCs are the preferred nonspecific hemostatic agent for NOAC reversal; they are plasma-derived products that contain three (factors II, IX, and X) or four (factors II, IX, X, and VII) clotting factors, in addition to variable amounts of heparin and the natural coagulation inhibitors protein C and protein S. Animal studies have demonstrated that PPCs have a variable ability to normalize anticoagulation parameters and to prevent or attenuate bleeding seen with NOAC usage. 14,[19][20][21][22][23][24][25] The limited data available in humans are restricted to healthy volunteers only. In three small, randomized, placebo-controlled studies involving between 12 and 93 patients, PCC use reversed the anticoagulant effects of rivaroxaban and edoxaban, but not of dabigatran.…”
Section: General Supportive Measuresmentioning
confidence: 99%
“…Use of dabigatran was associated with a reduced risk of intracranial hemorrhage (hazard ratio [HR] = 0.34, 95 % CI 0.26-0.46) and death (HR = 0.86, 95 % CI 0.77-0.96) and an increased risk of major gastrointestinal bleeding (HR = 1.28, 95 % CI 1.14-1. 44) [4].…”
Section: Major Bleeding In Patients Receiving Tsoacsmentioning
confidence: 99%
“…Human studies (dabigatrantreated healthy volunteers) PCC No reduction in blood loss after tail transection in mice [44] Reduced intracranial hematoma expansion and 24-hr mortality in mice [45] Reduced blood loss following kidney incision in rabbits [46] Reduced bleeding time, but not coagulation tests in rat tail transection model [18] Corrected some TG indices [25] Corrected PT, aPTT, TT and some TG indices [13] No correction of Hemoclot assay [13] No correction of aPTT, ECT, TT [9] aPCC No reduction in blood loss after tail transection in mice [44] Reduced bleeding time, but not coagulation tests in rat tail transection model [18] Corrected some TG indices [25] Corrected PT, aPTT and some TG indices [13] [23],…”
Section: Reversal Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 In general, fewer studies found FVIIa to be effective than PCC or aPCC, and some studies found both PCC and FVIIa to be without benefit. 33 The reason for the inconsistent findings with FVIIa might be explained by the fact that in vitro studies suggest that FVIIa can reverse the effect of dabigatran at therapeutic levels, but the effectiveness of FVIIa declines as the dabigatran levels increase. 34 The animal models for studying reversal used a range of NOAC doses, with those using extremely high levels of dabigatran being less likely to show effective reversal.…”
Section: Do We Really Need Antidotes For Noacs?mentioning
confidence: 99%